2014
DOI: 10.1038/icb.2014.4
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptors and NLRP3 as central regulators of pancreatic islet inflammation in type 2 diabetes

Abstract: The global health and economic burden of type 2 diabetes (T2D) has reached staggering proportions. Current projections estimate that 592 million people will have diabetes by 2035. T2D-which comprises 90% of cases-is a complex disease, in most cases resulting from a combination of predisposing genes and an unhealthy environment. Clinical onset of the disease occurs when pancreatic β cells fail in the face of insulin resistance. It has long been appreciated that chronic activation of the innate immune system is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 130 publications
(247 reference statements)
0
45
0
1
Order By: Relevance
“…Recent work has shown that the amyloid ␤ found in the plaques present in the brains of AD patients activates the NLRP3 inflammasome, leading to the production of IL-1␤ (39,40). Further studies also determined that two other human amyloids, IAPP and SAA, are also recognized by NLRP3 (29)(30)(31). In order to determine if the bacterial amyloid curli could also induce secretion of IL-1␤, BMDMs from wild-type C57BL/6 mice were stimulated for 24 h with a dose titration (0 to 10 g/ml) of curli fibers.…”
Section: Curli Fibers Induce Secretion Of Il-1␤mentioning
confidence: 96%
See 1 more Smart Citation
“…Recent work has shown that the amyloid ␤ found in the plaques present in the brains of AD patients activates the NLRP3 inflammasome, leading to the production of IL-1␤ (39,40). Further studies also determined that two other human amyloids, IAPP and SAA, are also recognized by NLRP3 (29)(30)(31). In order to determine if the bacterial amyloid curli could also induce secretion of IL-1␤, BMDMs from wild-type C57BL/6 mice were stimulated for 24 h with a dose titration (0 to 10 g/ml) of curli fibers.…”
Section: Curli Fibers Induce Secretion Of Il-1␤mentioning
confidence: 96%
“…NLRP3 is the best-characterized inflammasome; it can be activated by a wide range of danger signals and uses apoptosis-associated speck-like protein containing a CARD (ASC) as an adaptor molecule (26). Recently, human amyloid ␤, islet amyloid polypeptide, and SAA have all been demonstrated to activate the NLRP3 inflammasome, resulting in the production of IL-1␤ (29)(30)(31).…”
mentioning
confidence: 99%
“…The loss of ASC (Pycard), a critical adaptor required for the assembly of NLRP3, substantially improved insulin action and secretion by ameliorating the production of pancreatic IL1β and β-cell death caused by a long term HFD in mice 101 . The NLRP3 inflammasome, TLR2, and TLR4 are triggers for islet inflammation in T2DM and the activation of macrophages in various tissues is also mediated by activation of the NLRP3 inflammasome 102 . Pancreatic β-cell failure in the Zucker diabetic fatty rat is associated with activation of NLRP3-ASC infammasome in M1 macrophages infiltrating into pancreatic islets 103 .…”
Section: [H3] Nod2mentioning
confidence: 99%
“…Recent studies demonstrate that macrophages derived from circulating MNC infiltrate pancreatic islets in primates (39) and humans with T2D (15) and disrupt pancreatic insulin secretion. Indeed, TNF-␣ from MNC-derived macrophages activates NF-B within the ␤-cell thereby inducing endoplasmic reticulum stress and subsequent ␤-cell apoptosis (50). We recently reported a link between hyperglycemia-induced MNC oxidative stress and low first-phase ␤-cell function in women with and without PCOS (34) and proposed that inflammation may trigger attenuated ␤-cell function in women with PCOS.…”
mentioning
confidence: 99%
“…Activated NF-B dissociates from inhibitory-B (IB) in the cytoplasm and undergoes nuclear translocation to promote the transcription of tumor necrosis factor-␣ (TNF-␣), a proinflammatory cytokine known to impair insulin signaling and action (46). Although the link between insulin resistance and inflammation in the pathogenesis of T2D is well established, inflammation may also play an important role in disrupting pancreatic insulin secretion (13,50). Within the ␤-cell, there is a readily available pool of insulin released upon initial glucose ingestion (1st phase) that is followed by synthesis of new insulin to manage postprandial glucose fluctuations (2nd phase) (30).…”
mentioning
confidence: 99%